MENAGIH HAK BERAGAMA MUSLIM AHMADIYAH DAN SYIAH SAMPANG DALAM PERSPEKTIF NALAR MAQÂṢIDÎ - Nasrullah Ainul Yaqin (UIN Sunan Kalijaga Yogyakarta, 2020)
This article responds to the issue of human rights (HAM) from the perspective of maqâṣidî’s reasoning (maqâṣid asy-syarî‘ah). Considering that human rights violations have always been being a boomerang in the life of Indonesian society. It could be seen like what happened to the Shia people in Sampang whose right have been lost to enjoy their life in peace and worship their religious rights freely and safely in their homeland. A similar case has been experienced by several Ahmadiyah congregations. In this case, the writer elaborates the maqâṣid concept which has been continued its development along the time. According to ‘Izzuddin bin ‘Abd as-Salâm, the purpose of Islamic law is to create benefit and reject the damage for human being, both in this world and in the hereafter. The highest benefit of Islamic law is to maintain and keep the religion (ḥifẓ ad-dîn), soul (ḥifẓ an-nafs), reason (ḥifẓ al-‘aql), descent (ḥifẓ an-nasl), and property (ḥifẓ al-mâl) . These five things are known as aḍ-ḍarûriyyah al-khamsah (the five primary). Later, some maqâṣidî scholars (such as Ibn ‘Âsyûr, ‘Allâl al-Fâsî, Jamâluddîn ‘Aṭiyyah, and Yusûf al-Qarâḍâwî) developed the scope of maqâṣid asy-syarî‘ah. So that, it is not restricted to the five primary matters only, but also to several other primary matters, such as justice, freedom, equality and human rights. On the other side, Muḥammad az-Zuḥailî views that the concept of aḍ-ḍarûriyyah al-khamsah is the basis of human rights itself. Because, ḥifẓ ad-dîn, ḥifẓ an-nafs, ḥifẓ al-‘aql, ḥifẓ an-nasl, and ḥifẓ al-mâl do not only mean to maintain, but also include the meaning of rights, namely: the right to religion, the right to life, the right to think and freedom of thought, family rights, and property rights.